Serum Ammonia in Associated With Transplant-free Survival in Hospitalized Patients With Acutely Decompensated Cirrhosis. Issue 4 (April 2016) - Patwardhan, Vilas R.; Jiang, Zhengui G.; Risech-Neiman, Yesenia; Piatkowski, Gail; Afdhal, Nezam H.; Mukamal, Kenneth; Curry, Michael P.; Tapper, Elliot B.
Abstract : Background: As ammonia metabolism is a complex multiorgan process, we sought to determine whether serum ammonia concentrations were associated with transplant-free survival in patients with acutely decompensated cirrhosis and acute-on-chronic liver failure (ACLF). Methods: We studied 494 consecutive patients hospitalized with cirrhosis between April 2007 and September 2012 with venous ammonia measured on hospital admission. The primary outcome was transplant-free survival. Results: Overall, rates of death or transplant within 30 and 90 days were 23.1% (n=114) and 37.7% (n=186), respectively. Forty-six patients (9.2%) underwent liver transplantation within 90 days. In a multivariate Cox proportional hazards model, ammonia concentration was independently associated with death or transplantation within 30 and 90 days after adjusting for model for end-stage liver disease, sodium, white blood cells, and number of ACLF organ failures; every doubling of ammonia was associated with respective hazard ratios of 1.22 (95% confidence interval, 1.03-1.38) and 1.21 (95% confidence interval, 1.04-1.44) for 90- and 30-day transplant or mortality. Notably, after adjusting for ammonia, organ failures were not predictive of outcomes. In a Kaplan-Meier analysis, patients with admission ammonia concentrations >60 μmol/L had significantly lower 90-day transplant-free survival ( P =0.0004). Patients with admission ammonia concentrations >60 μmol/L had higher 90- and 30-day risk of death or transplantation (45.2% vs. 31.2%, P =0.001; and 31.6% vs. 15.7%, P <0.0001, respectively). Conclusion: For patients with acutely decompensated cirrhosis, an elevated serum ammonia concentration on admission is associated with reduced 90-day transplant-free survival after adjusting for established predictors.